DESIGN & DEVELOPMENT OF WIRELESS SENSOR NETWORK BASED MONITORING SYSTEM TO MONITOR THE STRENGTH AND LIFETIME OF BRIDGES AND FLYOVERS - S, Rajeshwari; Pushparathi, V.Gladis; H B, Sushmitha; H, Spoorthi (The journal of contemporary issues in business and government, 2021)
Bridge’s tracking gadget is a crucial for bridge, flyover, and railway bridge safety diagnostics. The monitoring machine adopts a 3-level distributed structure Which consists of treasured server, clever acquisition node, and close by controller. Domains are distributed over the bridges, and one local controller manages all nodes. A 24-bit A / D conveyor to get high precision data. The proposed architecture has two characteristics as opposed to the conventional process. The node is by and large a clever tool based on a sturdy DSP processor. Field sensor signals are processed and compressed to the node in real time. Just IEEE802.11 wireless network sends out the processing results to the device. This process will ease substantial server load and decrease communication bandwidth calling. Second, 3 G Wireless community is used to provide ample bandwidth between controller and server for the real-time data transmission. This running monitoring system shows the system being proposed is steady and utilitarian .